Chemical methods for processing nanomaterials - Singh, Vidya Nand, 1976- ([Place of publication not identified] CRC Press, 2020)
"The book Chemical Processing Nanomaterials discusses the latest advancements in the processing of various types of nanomaterials. The main objective of the book is to provide the reader with a comprehensive review of the latest advances in synthesis as well as processing of almost all kinds of nanomaterials using various physical and chemical methods. The book includes chapters on Chemical Methods such as microemulsions, colloidal route, wet chemical method, chemical vapor deposition technique, sol-gel method, electrodeposition for growing different kinds of nanomaterials including Chalcogenides, Metal Oxide nanostructures, perovskite nanocrystals, nano structures on patterned electrode, Low Dimensional Carbon Nanomaterials and applications at Nanoscale"--
Chemical methods for processing carbon nanomaterials / Sehmus Ozden -- Synthesis of nanomaterials and nanostructures / Preeti Kaushik, Amrita Basu and Meena Dhankhar -- Wet chemical methods for nanoparticle synthesis / Abhijit Jadhav -- Electrodeposition : a versatile and robust technique for synthesizing nanostructured materials / Pravin S. Shinde and Shanlin Pan -- Nanostructured materials using microemulsions / Sonalika Vaidya -- Methods of manufacturing composite materials / Anton Yegorov, Marina Bogdanovskaya, Olga Zhdanovich, Vitaly Ivanov and Daria Gudeeva -- Quantum dots and their synthesis processes / Prashant Ambekar and Jasmirkaur Randhawa -- Chemical vapor deposition (CVD) technique for nanomaterials deposition / Abhishek K. Arya, Rahul Parmar, K.S. Gour, Decio B. de F.N., R. Gunnella, J.M. Rosolen and V.N. Singh -- CVD growth of transition metal dichalcogenides MX2 (M:Mo, W, X:Se, S) / Alejandro Fajardo Peralta, Jose Valenzuela-Benavides, Nestor Perea-Lopez, and Mauricio Terrones -- Metal oxide/CNT/graphene nanostructures for chemiresistive gas sensors / Sanju Rani, Manoj Kumar, Yogesh Kumar, Rahul Kumar and V.N. Singh -- Chemical route synthesis and properties of CZTS nanocrystals for sustainable photovoltaics / Shefali Jain, Pooja Semalti, V.N. Singh and S.N. Sharma -- Surface modification of glass nanofillers and their reinforcing effect in epoxy-based nanocomposites / Lifeng Zhang and Demei Yu -- Gas sensor application of zinc oxide / Bharat R. Pant and Ahalapitiya H. Jayatissa -- Titanium dioxide as a photo catalyst material : a review / Yogesh Singh, Sanju Rani, Manoj Kumar, Rahul Kumar and V.N. Singh.
OCLC-licensed vendor bibliographic record.
Keywords: Nanostructured materials; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Life Sciences / General